2015
DOI: 10.1177/2040206614566582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of L-lysine amino acid on the HIV-1 RNA replication in vitro

Abstract: The results show that L-lysine amino acid excess is characterized by significant increased of HIV-1 RNA copies in enriched peripheral blood mononuclear cells plasma samples of HIV-infected patients. There was evidence for an association between L-lysine supplementation and HIV-1 RNA replication and the level changes of this host essential nutritional element play a key role in the synthesis of the virus proteins and in transcription initiation of the retrovirus life cycle. High intake of L-lysine amino acid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…The findings from previous studies seem to support our hypothesis. In particular, we found that the L-lysine amino acid levels were negatively correlated with viral load [ 93 ] and the excess of this amino acid in plasma samples leads to active HIV replication in vitro [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from previous studies seem to support our hypothesis. In particular, we found that the L-lysine amino acid levels were negatively correlated with viral load [ 93 ] and the excess of this amino acid in plasma samples leads to active HIV replication in vitro [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysine is another amino acid that has been shown to play an important role on viral infections. It is essential for the replication of viruses and progression of infections [ 57 , 58 , 59 ]. The extra- and intracellular concentrations of l -lysine amino acid play a limiting role in the synthesis of the virus proteins and in transcription initiation of the retrovirus life cycle, and the deficiency of this essential nutritional element can reduce viral load [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated serious changes in plasmatic concentrations of l -lysine in HIV-infected patients, where it was found that plasma concentrations of l -lysine were negatively correlated with HIV-1 RNA levels and inversely with CD4 lymphocytes count. Therefore, an excess of l -lysine concentration leads to active HIV replication and reduces the concentration of plasma amino acid [ 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the antiviral activity of TSV-LAO does not affect infected cells via generation of hydrogen peroxide but rather by intermediate product or substrate depletion. L-Lys excess is characterized by a significant increase in HIV-1 RNA copies in enriched peripheral blood mononuclear cell fractions of HIV-infected patients and the copy number did not increase after adding L-Lys with LysOX in the plasma samples (Butorov 2015 ). Therefore, we consider that LysOX is a suitable antiviral as well as antibacterial agent.…”
Section: Perspectives For Possible Biomedical Applicationsmentioning
confidence: 99%